Analisis Asuhan Keperawatan Kritis Pada Ny. M Diagnosa Medis Post Op Ctr Edema Cerebri Dengan Penerapan Cpr Terhadap Gangguan Sirkulasi Spontan di ICU Rsud Ulin - Rani Normaya Sari; M. Sobirin Mohtar; Bagus Rahmat Santoso; Rani, Rani Normaya Sari (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Cerebral edema is a condition caused by hematoma enlargement with progressive intracranial pressure. This condition requires hematoma evacuation through craniotomy surgery so that it can cause spontaneous circulation disorders and this condition tends to be life-threatening because the clinical condition of the body will experience a worsening condition so that life-saving efforts are needed by providing actions in the form of CPR (Cardio Pulmonary Resuscitation) or cardiopulmonary resuscitation (CPR) which aims to increase the chances of survival of someone who experiences cardiac arrest. This study aims to analyze critical nursing care for Mrs. M with a medical diagnosis of Post Op CTR Cerebral Edema with the application of CPR to Spontaneous Circulation Disorders in the ICU of Ulin Hospital. This research method is qualitative with a descriptive case study type with a holistic single case study design that explores a particular case in depth by involving the collection of various sources of information. The results obtained in Mrs. M after being given CPR by combining compression with ventilation for 2 minutes or 5 cycles for spontaneous circulation disorders were that the patient did not respond, the carotid pulse was not palpable, there was no breathing, the patient's condition showed rigor mortis and the ECG showed asystole. CPR was stopped when signs of biological death were found and collaborated with the medical team for advanced life support. There was no effect of CPR on nursing care for spontaneous circulation disorders in Post Op CTR Edema Cerebri patients.